2019
DOI: 10.1038/s41598-019-43824-0
|View full text |Cite
|
Sign up to set email alerts
|

Walking and finger tapping can be done with independent rhythms

Abstract: Rhythmic movements occur in many aspects of daily life. Examples include clapping the hands and walking. The production of two independent rhythms with multiple limbs is considered to be extremely difficult. In the present study we evaluated whether two different, independent rhythms that involved finger tapping and walking could be produced. In Experiment I, twenty subjects that had no experience of musical instrument training performed rhythmic finger tapping with the right index finger and one of four diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
(55 reference statements)
1
11
0
1
Order By: Relevance
“…This decoupling was interpreted as being functional, that is, to enable the drum beat rhythm to be maintained. Additional evidence for decoupling of rhythmical upper limb actions from other body movement rhythms emerged from the study of Qi et al [48] in which nonmusicians performed rhythmic finger tapping in combination with self-paced walking, given-paced walking, alternative bilateral heel tapping, and heel tapping with one foot ipsilateral to the tapping Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 24 February 2020 doi:10.20944/preprints202002.0340.v1…”
Section: Discussionmentioning
confidence: 99%
“…This decoupling was interpreted as being functional, that is, to enable the drum beat rhythm to be maintained. Additional evidence for decoupling of rhythmical upper limb actions from other body movement rhythms emerged from the study of Qi et al [48] in which nonmusicians performed rhythmic finger tapping in combination with self-paced walking, given-paced walking, alternative bilateral heel tapping, and heel tapping with one foot ipsilateral to the tapping Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 24 February 2020 doi:10.20944/preprints202002.0340.v1…”
Section: Discussionmentioning
confidence: 99%
“…This decoupling was interpreted as being functional, that is, to enable the drum beat rhythm to be maintained. Additional evidence for decoupling of rhythmical upper limb actions from other body movement rhythms emerged from the study of Qi et al [37] in which non-musicians performed rhythmic finger tapping in combination with self-paced walking, given-paced walking, alternative bilateral heel tapping, and heel tapping with one foot ipsilateral to the tapping finger. It was found that the walking conditions were independent of the finger tapping, but the heel tapping was not.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of a rhythmic beat induces synchronization of human movements with the beats [ 13 , 15 , 32 , 33 ], and rhythmic body motions are thus modified through the interaction with the external environment, tending towards entrainment [ 34 ]. To prevent this entrainment, one limb must move in an automatic mode by utilizing central pattern generators (CPGs), which are neural circuits producing rhythmic motor movements, such as, walking and swimming, to produce rhythmic movements, whereas the other limb movements are processed through brain activities [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%